(untitled) (Journal of Agriculture and Environment, 2022)
As maize is a C4 plant it is expected to have greater productivity however, its production and productivity are not found to its potential. Therefore, to evaluate the effect of detasseling and defoliation to increase the productivity, a field experiment was conducted on sweetcorn at Khotang, Nepal in 2021. The study was executed in Randomized Complete Block Design (RCBD) with three replications and seven treatments. The results revealed that number of kernels (608.46), number of rows (15.20), 1000 grains weight (210.68gm) were recorded significantly higher in the plot where 50% plants were detasselled. It clearly shows that 50% detasseling is one of the best options to enhance the yield of sweetcorn followed by detasseling + defoliation of all leaves leaving three leaves below the ear.